2022
DOI: 10.4269/ajtmh.21-0744
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Pattern of COVID-19–Related Mortality during the First Year of the Pandemic in Brazil: A Population-based Study in a Region of High Social Vulnerability

Abstract: Currently, the world is facing a severe pandemic caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Although the WHO has recommended preventive measures to limit its spread, Brazil has neglected most of these recommendations, and consequently, our country has the second largest number of deaths from COVID-19 worldwide. In addition, recent studies have shown the relationship between socioeconomic inequalities and the risk of severe COVID-19 infection. Herein, we aimed to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…91% (86 of 95) of the studies 20 , 21 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , ...…”
Section: Covid-19 Mortality and Deprivationunclassified
See 1 more Smart Citation
“…91% (86 of 95) of the studies 20 , 21 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , ...…”
Section: Covid-19 Mortality and Deprivationunclassified
“…In Brazil, positive associations were found between social disadvantage and COVID-19 mortality rates in all 12 studies conducted at different timepoints. 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 126 For example, de Souza and colleagues 97 (up to May 6, 2020) and Silva and Ribeiro-Alves 101 (up to May 23, 2020) found that people living in high-income areas were more at risk of COVID-19 infection, but those living in more deprived areas had higher death rates. Studies from Chile, 104 Columbia, 105 and Mexico 106 , 107 all observed positive associations between indicators of social disadvantage and COVID-19 mortality rates.…”
Section: Covid-19 Mortality and Deprivationmentioning
confidence: 99%
“…Similar temporal groupings during that era have been observed in previous studies, for example, in Brazil [ 102 ]. Iran has previously dealt with a variety of diseases, but COVID-19 stunned the system with its severity, rapid spread, and pathological consequences [ 103 ]. COVID-19 vaccination did not begin until late February 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the study's limitations, it was not possible to investigate the association between some variables such as education and main associated symptoms and the outcome of death from COVID-19 due to the unavailability of some information in the database used in our study. Another relevant limitation is the possibility of underreported cases and deaths, an issue reported in prior studies in Brazil [4,66], the European continent, and South Africa [67]. Mortality information is crucial in understanding the spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%